Chest Physiotherapy in Children with Bronchopeumonia at Kardinah Regional Hospital, Tegal City - Istiqomah Fi Laella, Nurul; Murniati, Murniati (Universitas Ibn Khaldun Bogor, 2024)
Background: Bronchopneumonia is a type of pneumonia in which the bronchi and alveoli experience infection or inflammation. Inflammation in cases of bronchopneumonia usually results in increased sputum production until signs such as high fever, shortness of breath, dry and productive cough appear, causing problems to arise, one of which is ineffective airway clearance. Objective: To determine whether airway clearance nursing care is ineffective with chest physiotherapy in children with bronchopeumonia in the Wijayakusuma ward at Kardinah Hospital, Tegal City. Method: This case study uses the case study method, with interview techniques, observation and physical examination. This research was carried out at Kardinah Tegal Regional Hospital for 3 days (5 to 7 February 2024). Results: The results of the case study of pediatric patients with bronchopneumonia experienced changes on the third day after being given chest physiotherapy therapy, with the result that coughing was reduced and phlegm was able to come out, RR: 24x/minute, rhonchi breath sounds were reduced. Conclusion: From the results of the nursing evaluation on the third day, the problem of ineffective airway clearance was resolved using chest physiotherapy therapy.